Corrupção e participação política nas Américas e no Caribe: 2004-2012 - Robert Bonifacio da Silva (2014)
The research investigates the role of corruption in political participation among americans and caribbeans from theoretical and empirical analysis. The rounds of 2004, 2006-7, 2008, 2010 and 2012 of America´s Barometer are used. By discussion of studies on political participation, we suggest a definition and select up empirical indicators. The multidimensional nature of political participation is detected, with the presence of five distinct forms: community activism, electoral activism, contact with political and governmental actors, voter turnout and activism of protest. Two indicators of corruption are used: experience and intolerance with corruption. We note that intolerance is more frequently than experience. In statistical tests, we observe that experience with corruption has a positive effect on participation and that intolerance has a negative effect, being the predominant discordant results with the specialized literature.